Global DNA Methylation in the Chestnut Blight Fungus Cryphonectria parasitica and Genome-Wide Changes in DNA Methylation Accompanied with Sectorization - So, Kum-Kang; Ko, Yo-Han; Chun, Jeesun; Bal, Jyotiranjan; Jeon, Junhyun; Kim, Jung-Mi; Choi, Jaeyoung; Lee, Yong-Hwan; Huh, Jin Hoe; Kim, Dae-Hyuk (Frontiers in Plant Science, 2018)
Mutation in CpBck1, an ortholog of the cell wall integrity mitogen-activated protein kinase kinase kinase (MAPKKK) of Saccharomyces cerevisiaee, in the chestnut blight fungus Cryphonectria parasitica resulted in a sporadic sectorization as culture proceeded. The progeny from the sectored area maintained the characteristics of the sector, showing a massive morphogenetic change, including robust mycelial growth without differentiation. Epigenetic changes were investigated as the genetic mechanism underlying this sectorization. Quantification of DNA methylation and whole-genome bisulfite sequencing revealed genome-wide DNA methylation of the wild-type at each nucleotide level and changes in DNA methylation of the sectored progeny. Compared to the wild-type, the sectored progeny exhibited marked genome-wide DNA hypomethylation but increased methylation sites. Expression analysis of two DNA methyltransferases, including two representative types of DNA methyltransferase (DNMTase), demonstrated that both were significantly down-regulated in the sectored progeny. However, functional analysis using mutant phenotypes of corresponding DNMTases demonstrated that a mutant of CpDmt1, an ortholog of RID of Neurospora crassa, resulted in the sectored phenotype but the CpDmt2 mutant did not, suggesting that the genetic basis of fungal sectorization is more complex. The present study revealed that a mutation in a signaling pathway component resulted in sectorization accompanied with changes in genome-wide DNA methylation, which suggests that this signal transduction pathway is important for epigenetic control of sectorization via regulation of genes involved in DNA methylation.